Evaluasi Kinerja Jaringan Distribusi Air Bersih Distrik Aimas Kabupaten Sorong Menggunakan Software Epanet 2.0 - Sarluf, Perwira Budiman; Pamudjianto, Agung (LRI Universitas Muhammadiyah Sorong, 2023)
The Sorong Regency Government, through related agencies, is building, operating and maintaining a clean water distribution network in Sorong Regency, considering that population growth continues to increase and limited raw water sources have caused the clean water distribution system in Aimas District to experience several problems so that its operation cannot run optimally. This research aims to evaluate the performance of clean water distribution in the Aimas District, Sorong Regency in meeting the clean water needs of the Aimas District community. The method used is to collect primary and secondary data and then analyze it using Epanet 2.0 software to simulate the condition of the distribution network system in the research area. Based on the results of calculations, the raw water discharge in the research area is smaller than the customer's water discharge, the delivery time for clean water does not run consistently, serving the water needs of areas outside the Aimas District, so the water needs of the people in the Aimas District cannot be fully met. Simulation results using Epanet 2.0 software show that unstable flow velocity causes a decrease in flow velocity in the clean water distribution network system in Aimas District.